Crossing the Frontier : Photographs of the Developing West, 1849 to the Present. - Betsky, Aaron; Lane, John R.; Moores, Eldridge M.; Phillips, Sandra S.; Rodriguez, Richard (San Francisco : San Francisco Museum of Modern Art, 1996)
Adams, Ansel ; Adams, Robert ; Alderson, W.W. ; Arndt, Thomas Frederick ; Babbitt, J.P. ; Baltz, Lewis ; Banks, E.J. ; Bartscherer, Joseph ; Beahan, Virginia ; Becher, Max ; Bell, William ; Boland, M.D. ; Bosse, Henry P. ; Bosworth, Barbara ; Studio, Bryan ; Studio, Bunnell ; Butcher, Solomon ; Cameron, Evelyn J. ; Conner, Lois ; Conniff, Gregory ; Curtis, Asahel ; Curtis, Charles C. ; Dane, William Thacher ; Davis, O.T. ; Dawson, Robert ; Deal, Joe ; Delano, Jack ; Divola, John ; Easterly, Thomas M. ; Edgerton, Germeshausen & Grier, Inc. ; Ericson, Augustus William ; Evans, Terry ; Faust, Christopher ; Fiske, George ; Friedlander, Lee ; Ganis, John ; Gardner, Alexander ; Garnett, William ; Gohlke, Frank ; Goin, Peter ; Goldbeck, Eugene O. ; Gudmundson, Wayne ; Halverson, Karen ; Hanson, David T. ; Hart, Alfred A. ; Harvey, Tim ; Haynes, Frank Jay ; Hernandez, Anthony ; Hook, William E. ; Houseworth & Co., Thomas ; Huffman, Laton Alton ; Humble, John ; Jackson, William Henry ; James, Geoffrey ; Jenshel, Len ; Johnson, George Howard ; Kennedy, Gene ; Kinsey, Darius R. ; Klett, Mark ; Photo, Larson ; Bureau, Las Vegas News ; Lawrence and Houseworth ; Lee, Russell ; Lueders-Booth, Jack ; McAuley, Skeet ; McClure, L.C. ; MacGregor, Greg ; McPhee, Laura ; Meisinger Jr., Richard ; Miller, Francis ; Misrach, Richard ; Newman, Almeron ; Norfleet, Barbara ; Bros, Olson ; O'Sullivan, Timothy H. ; Company, Pacific Photo ; Paddock, Eric ; Palmer, Alfred ; Patteson, Harvey ; Patteson, Julius ; Pfahl, John ; Robbins, Andrea ; Rothstein, Arthur ; Russell, Andrew Joseph ; Ruwedel, Mark ; Savage, Charles Roscoe ; Shambroom, Paul ; Shipler's Commercial Photographers ; Shrew, William ; Steale, Charles ; Sternfeld, Joel ; Stimson, J.F. ; Chi, T'seng Kwong ; Watkins, Carleton E. ; etc.
Crossing the Frontier : Photographs of the Developing West, 1849 to the Present, San Francisco Museum of Modern Art, San Francisco, September 26, 1996 - January 28, 1997 ; Yale University Art Gallery, April 11 - June 8, 1997 ; Phoenix Art Museum, July 12 - September 27, 1997 ; Tokyo Metropolitan Museum of Photography, February 11 - April 3, 1998
Engels
boek